Studies of Fossilization in Second Language Acquisition - Han, Zhaohong 1962-; Odlin, Terence (Second Language Acquisition, 2005)
This volume, as a sequel to Fossilization in Adult Second Language Acquisition by Han (2004), brings together a collection of most recent theoretical and empirical studies on fossilization, a classic problem of second language acquisition. It covers a wide range of perspectives and issues. The analyses discussed herein address key concerns of many second language researchers and teachers with regard to just how far anyone can go in learning a new language